Influence of the quality of drinking water supply sources on the formation of the ecologically-dependent pathology of the population of the Republic of Dagestan - M. G. Daudova; R. B. Bagomedova; K. K. Bekshokov; M. M. Medzhidova; S. M. Nakhibashev; P. A. Bekshokova; A. G. Gasangadzhieva (Юг России: экология, развитие)
Aim. Study of the influence of drinking water quality on the ecologically-dependent morbidity of the population of the Republic of Dagestan.Material and Methods. Methods of current and retrospective analysis of regional health indicators and methods of mathematical-statistical and medical-geographical analysis were used. Statistical processing of the results was carried out using the STATISTICA and Excel software packages. When carrying out laboratory studies on the quality of drinking water, we used a Lumex atomic absorption spectrometer "MGA-915MD".Results. Numerous hygiene studies indicate the direct impact of unsatisfactory drinking water quality on the health of a population. The relationship between sanitary and chemical indicators and the incidence rate for a number of nosological forms has been proven. It is generally accepted that human health is influenced by lifestyle factors (working, living and relaxation conditions), heredity and the ecological condition of the area of residence, including the quality of drinking water. Although it is not possible to differentiate the share of the negative effect caused by the consumption of poor quality drinking water but the incidence of certain nosological forms (cancer of the esophagus, gastrointestinal tract and kidney diseases) in the those regions of the Republic of Dagestan under consideration correlates with the characteristics of drinking water.Conclusion. The problem of pollution of water supply sources for the population in the dynamics of the long-term remains a priority concern. The quality and safety of drinking water are decreasing, which cannot but have a negative impact on public health. Correlation linkages between indicators of drinking water quality and oncological morbidity of the population were also established in indicators below the maximum permissible concentrations, which corresponds to a typical logistic model of causal relationships and serves as evidence of the high dependence of health disorders on chemical contamination of water supply sources.